# (-2y+5)(-2y+5)=0

## Simple and best practice solution for (-2y+5)(-2y+5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (-2y+5)(-2y+5)=0 equation:

Simplifying
(-2y + 5)(-2y + 5) = 0
Reorder the terms:
(5 + -2y)(-2y + 5) = 0
Reorder the terms:
(5 + -2y)(5 + -2y) = 0
Multiply (5 + -2y) * (5 + -2y)
(5(5 + -2y) + -2y * (5 + -2y)) = 0
((5 * 5 + -2y * 5) + -2y * (5 + -2y)) = 0
((25 + -10y) + -2y * (5 + -2y)) = 0
(25 + -10y + (5 * -2y + -2y * -2y)) = 0
(25 + -10y + (-10y + 4y2)) = 0
Combine like terms: -10y + -10y = -20y
(25 + -20y + 4y2) = 0
Solving
25 + -20y + 4y2 = 0
Solving for variable 'y'.
Factor a trinomial.
(5 + -2y)(5 + -2y) = 0
Subproblem 1Set the factor '(5 + -2y)' equal to zero and attempt to solve:
Simplifying
5 + -2y = 0
Solving
5 + -2y = 0
Move all terms containing y to the left, all other terms to the right.
Add '-5' to each side of the equation.
5 + -5 + -2y = 0 + -5
Combine like terms: 5 + -5 = 0
0 + -2y = 0 + -5
-2y = 0 + -5
Combine like terms: 0 + -5 = -5
-2y = -5
Divide each side by '-2'.
y = 2.5
Simplifying
y = 2.5
Subproblem 2Set the factor '(5 + -2y)' equal to zero and attempt to solve:
Simplifying
5 + -2y = 0
Solving
5 + -2y = 0
Move all terms containing y to the left, all other terms to the right.
Add '-5' to each side of the equation.
5 + -5 + -2y = 0 + -5
Combine like terms: 5 + -5 = 0
0 + -2y = 0 + -5
-2y = 0 + -5
Combine like terms: 0 + -5 = -5
-2y = -5
Divide each side by '-2'.
y = 2.5
Simplifying
y = 2.5Solutiony = {2.5, 2.5}`